Food sovereignty towards rice sustainability - Rubiah Mohd Amin,; Haniff Ahamat,; Muhamad Sayuti Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysia should adhere to the WTO’s policy on agrifood trade liberalization. Agrifood regulations are designed to ensure the protection of farmers and achieve food sovereignty. This research investigates and plots the evolution of agrifood laws that promote food sovereignty and trade liberalization towards rice sustainability. The qualitative study is based on the application of social jurisprudence theory and secondary data. The structure list in the current legislation is mapped to the regulations and standard operations applied in the matrix table. Malaysia’s agrifood regulations are found to reinforce the WTO policy of liberalizing trade for agriculture, which undermines food sovereignty and provides inadequate protection for farmers. The interdependence of supporting sustainable agriculture and empowering small farmers is recognized by SDG2, which aims to address hunger, food security, nutrition, and climate change. The government should provide policies that improve the management of the food system to achieve food sovereignty. A review of the Control of Padi and Rice Act 1994 is necessary for creating new provisions on ‘seed’, which includes a provision on food sovereignty for individuals working in the rice industry. The development of people in agrifood to support their global market can be explained in another provision.